Where we belong : a novel - Giffin, Emily (St. Martin's Press, 2012)
Her carefully constructed life thrown into turmoil by the appearance of an eighteen-year-old girl with ties to her past, New York television producer Marian Caldwell is swept up in a maelstrom of personal discovery that changes both of their perceptions about family.